First insights into the evolution of neotropical anthomyiid flies (Diptera: Anthomyiidae). Issue 7 (3rd October 2021) - Gomes, Lucas Roberto Pereira; Souza, Diego de Santana; de Carvalho, Claudio José Barros
Abstract : Anthomyiidae is a family of flies distributed worldwide comprising approximately 2, 000 species, which, based on molecular analyses, belong to the Muscoidea grade. The phylogenetic data for this family are limited and the Neotropical lineages have never been studied at the molecular level. Herein, we present the first phylogenetic analyses of Anthomyiidae including Neotropical taxa. The resulting phylogenetic trees – inferred using maximum-likelihood and Bayesian criteria and based on two nuclear and three mitochondrial genes and 56 terminals, including 13 Neotropical anthomyiid species – confirmed Anthomyiidae as a monophyletic lineage and sister group of Scathophagidae, which is also monophyletic. The clade Coenosopsia + Phaonantho was not recovered as a sister group of the remaining anthomyiids, as previously indicated by the results of morphological analyses. These and other generic relationships are discussed in the light of morphological data from previous studies. The divergence time estimation suggested that after a split from the Oestroidea clade approximately 51.7 Ma, the radiation of Anthomyiidae + Scathophagidae began during the Eocene, with the oldest common ancestor of both families living approximately 40.5 Ma and with the oldest anthomyiid ancestor living approximately 36.8 Ma. The split of the clade Coenosopsia + Phaonantho was dated to the Oligocene ( c . 23 Ma). These results provide new insights into the timing and rate of anthomyiid and scathophagid fly evolution.